(3HOGFY GdRghQ aj hbGFY GdOghQs - (3Lhj RGOg , eMeO Hf GdjGS GdMfaj GdQhej, eMjj GdOjf,J (B954 (3g` s
(3ChdgG (B:s
(3GPcQ GHJOGA OhdI GdLQGcSI HeUQ hcGf Chdge Gdedc GdXGgQ HQbhb hjbGd ai HYV GdGNHGQ Cf CUd GdLQGcSI ef fSd LHdI Hf GdGjge s
(3BNQgG (B:s
(3GfJgi eG ChQOfGg ai gPG GdLRA Edi BNQ OhdI Gdedc GdefUhQ YKeGf Hf Gdedc GdXGgQ Lbeb jJdhg GdLRA GdKGef ai CNHGQ OhdI Gdedc GdGTQa GfjGd GdYdGi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B40 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B66s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B229s
Keywords: (3GdJGQjNs